As contribuições das atividades de pesquisa educativas e emancipadoras nas aulas de filosofia do ensino médio - Silva, José Wandregesílio dos Santos (2021)
Despite some reformulations in the last decades of the teaching-learning process in secondary education, there is still the prejudice of having the concept that the teacher, and especially the student, at this level of education is not a researcher. However, our practice as a professor of the discipline of Philosophy at the secondary level allows us to say that we cannot do without the research activity, especially when it comes to teaching Philosophy, since this discipline necessarily takes us to the path of research and clarification, and this occurs whether in the bachelor's degree or in the licentiate degree, as there is a tendency to consider that only the professor and/or bachelor's degree student, in our case, from the Philosophy Course, are researchers. Taking these considerations into account, our dissertation's central objective is to present the development of a research activity, which we consider educational and emancipatory, as an essential requirement in the teaching-learning process in Philosophy classes at secondary level, in order to understand whether such activity can really contribute to the enlightening, critical and emancipatory training of students in high school. This is a research carried out in a state public school that started from the need to propose a research activity for high school students in the discipline of Philosophy. We use the dialectical method in a qualitative approach based on a focus group through participant observation research. For this purpose, we formed a working group of ten students, in the counter shift, with the title Emancipar Study Group, in order to verify with these students if the research can sharpen their curiosity and taste for Philosophy and if it contributes to the clarification, training and emancipation of students. This group of studies was formed by students from different classes of the discipline of Philosophy at high school, for 1 year, through which we developed the research activities taking Adorno's thought from his work Educação e Emancipação. The meetings took place after classes, based on this work, where the issues that revolved around questions of clarification, autonomy and emancipation were discussed. To complete our research, at the end of the group's activities, we applied a questionnaire with the members of the study group about the research developed to know if the group's research activities contributed to their learning and to their enlightening formation, critical and emancipatory. The results obtained showed us that the group brought great contributions to the Philosophy classes since the students who participated in them brought to the classroom very interesting, enlightening and sharpening discussions for the debate and learning of the students in the class. In our final considerations, we could see that the focus group reached beyond our proposed objective since it awakened some students even to study Philosophy at the higher level. Furthermore, they showed the interest (students and school management where we work) for us to continue with the educational and emancipatory research activities expressed in the Emancipar Study Group, working on new themes and the thoughts of other philosophers. We believe that such considerations demonstrate a great level of contribution of educational and emancipatory research activities to the teaching of Philosophy at secondary level in our country.